SYNONYMS, ANTONYMS, EXPRESSIONS OF POLYSEMY AND SEMANTIC FIELDS (Universal International Scientific Journal, 2026)
This article presents the views on the semantic and pragmatic features of Utkir Hoshimov's works, which not only serve an artistic and aesthetic purpose, but also serve as an important means of expressing the writer's worldview, the harmony of national values ​​and modernity, and the importance of these aspects in ensuring the uniqueness of the writer's language, the aesthetic value of the literary text, and communicative contact with the reader.
Keywords: semantic and pragmatic features; aesthetic value; national spirit